The holistic development of elite male hockey players in Canada - Glaude, M.; Bloom, G. A.; Baker, J. (Psychology of Sport and Exercise, 2026)
The purpose of this study was to investigate the perspective of ice hockey coaches and administrators on factors supporting holistic development of 15-17-year-old male ice hockey players in Canada. Participants were six coaches and/or administrators who possessed extensive experience working with elite male players, with several holding overlapping coaching and administrative roles that provided a comprehensive perspective on elite player development. Each participant completed a semi-structured interview, and the data was examined through reflexive thematic analysis. The analysis revealed several persistent challenges to holistic development in Canadian hockey, including a deeply embedded win-at-all-costs culture and organizational structures and policies that prioritized short-term results over long-term athlete growth, alongside limited resources to support holistic coaching practices. At the same time, participants highlighted promising efforts at both the micro and macro levels of the hockey development landscape, including long-term, systematic planning of on- and off-ice development, intentional team culture-building to strengthen athletes' social and life skills, and national-level efforts to standardize and promote holistic development. Taken together, the findings indicate advancing holistic development in Canadian hockey will require coordinated system-wide action, including national leadership, provincial and branch-level alignment, and accessible tools that can support coaches and administrators in simultaneously fostering athletes` performance and psychosocial well-being.